Quarters : The Accommodation of the British Army and the Coming of the American Revolution - McCurdy, John Gilbert, 1972- (Book collections on Project MUSE., 2019)
"Examines both quartering British soldiers in America and how this led to the American Revolution and how debates that ensued shaped Americans' notions of military power and place. A transnational history that includes Canada and the Caribbean"--